2005
DOI: 10.1007/s00125-004-1660-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential involvement of adipocyte insulin resistance in obesity-associated up-regulation of adipocyte lysophospholipase D/autotaxin expression

Abstract: Aims/hypothesis: Autotaxin is a lysophospholipase D that is secreted by adipocytes and whose expression is substantially up-regulated in obese, diabetic db/db mice. The aim of the present study was to depict the physiopathological and cellular mechanisms involved in regulation of adipocyte autotaxin expression. Methods: Autotaxin mRNAs were quantified in adipose tissue from db/db mice (obese and highly diabetic type 2), gold-thioglucose-treated (GTG) mice (highly obese and moderately diabetic type 2), high-fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 12 publications
8
89
0
1
Order By: Relevance
“…After separating the adipocyte and SV fractions, we found that levels of Enpp2 expression were higher in adipocytes than in the SV fraction, as was reported previously (Fig. 1B) (17). Among the cell types present in the SV fraction, Pref1 + CD34 + preadipocytes expressed higher levels of ENPP2 than CD11b + F4/80 + macrophages or CD8 + T cells (Fig.…”
Section: Enpp2 Is Produced By Preadipocytes and Adipocytessupporting
confidence: 87%
See 1 more Smart Citation
“…After separating the adipocyte and SV fractions, we found that levels of Enpp2 expression were higher in adipocytes than in the SV fraction, as was reported previously (Fig. 1B) (17). Among the cell types present in the SV fraction, Pref1 + CD34 + preadipocytes expressed higher levels of ENPP2 than CD11b + F4/80 + macrophages or CD8 + T cells (Fig.…”
Section: Enpp2 Is Produced By Preadipocytes and Adipocytessupporting
confidence: 87%
“…4). On the other hand, it has also been reported that ENPP2 expression is elevated in adipose tissue from diabetic db/db mice and that DIO mice show no significant changes in ENPP2 expression (17). What's more, earlier studies produced contradictory results regarding BAT mass, locomotor activity, thermogenic profiles, and systemic metabolism (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…6B ), as expected from previous work ( 9 ). Adipose tissue is a major source of ATX in the circulation (37)(38)(39)(40), and therefore, we measured the expression of ATX mRNA in the mammary fat pads of the female mice. ATX mRNA was increased by about 5.5-fold in the ONO-8430506-treated mice and this was accompanied by 3-fold increase in the concentration of ATX protein in the plasma ( Fig.…”
Section: Inhibition Of Atx In Vivo Increases Adipose Tissue Atx Expresupporting
confidence: 58%
“…In contrast to the decreased plasma lysoPLD activity of ATX in fasted rats, progressively increased LPA production from LPC by lysoPLD activity was reported in 24-h incubated serum of rabbits fed with a high cholesterol-diet for different numbers of weeks up to 12, mainly due to an increased total LPC level. 26) Increased expression of ATX by the adipose tissue of patients exhibiting both insulin resistance and impaired glucose tolerance or type 2 diabetes associated with massive obesity was reported, 27) suggesting an increased release of ATX into the blood circulation, about half of which was estimated to be derived from adipose tissue. 28) Further, LPA 1 was reported to be involved positively in high-fat diet-induced obesity in mice.…”
Section: Discussionmentioning
confidence: 99%